2013
DOI: 10.1603/en12261
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Analysis of Potato Psyllid Haplotypes in the United States

Abstract: The potato psyllid, Bactericera cockerelli (Sulc) (Hemiptera: Triozidae), is an economically important pest of potato (Solanum tuberosum L.) crops across the western and central United States, as it is known to cause psyllid yellows disease and to transmit the bacterium that causes zebra chip disease. Recent genotyping of B. cockerelli collected during the 2011 potato growing season identified three psyllid haplotypes within the western and central United States according to their geographical regions: northwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…As it is known that susceptibility varies among potato varieties (Munyaneza et al 2011), this is not an unexpected Þnding. However, as TPPs can be migratory, populations sometimes expand after invading a Þeld , Swisher et al 2013, and planting time can inßuence disease severity , Munyaneza et al 2012. Additionally, Davis et al (2012) have demonstrated that settling behavior is inßuenced by both CLP infection and time since infection, while also indicating that ßowering phenology is correlated with TPP population performance.…”
Section: Discussionmentioning
confidence: 99%
“…As it is known that susceptibility varies among potato varieties (Munyaneza et al 2011), this is not an unexpected Þnding. However, as TPPs can be migratory, populations sometimes expand after invading a Þeld , Swisher et al 2013, and planting time can inßuence disease severity , Munyaneza et al 2012. Additionally, Davis et al (2012) have demonstrated that settling behavior is inßuenced by both CLP infection and time since infection, while also indicating that ßowering phenology is correlated with TPP population performance.…”
Section: Discussionmentioning
confidence: 99%
“…Current research efforts seek to better understand the interactions among Liberibacter, the potato psyllid, and host plants. These interactions include variations among potato varieties in their resistance or tolerance to the disease, variations among psyllid populations and life-stages in their ability to acquire and transmit Liberibacter, and how geographic distributions influence overwintering of Liberibacter and psyllids (Munyaneza 2012, Cooper et al 2013, Swisher et al 2013a, 2013b). An important application of understanding these interactions is the ability to accurately diagnose Liberibacter infection in plants in the absence of visual symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Population mapping studies have identified three distinct potato psyllid haplotypes within the United States that are associated with three different geographical regions: Central, Western, and Northwestern ( Liu et al 2006 ; Swisher et al 2012 , 2013 ). Psyllids of the Central haplotype have been identified across a large geographical range, spanning from eastern Mexico up to Texas, Kansas, Colorado, Nebraska, and Wyoming, all the way to North Dakota ( Swisher et al 2012 , 2013 ).…”
mentioning
confidence: 99%
“…Psyllids of the Central haplotype have been identified across a large geographical range, spanning from eastern Mexico up to Texas, Kansas, Colorado, Nebraska, and Wyoming, all the way to North Dakota ( Swisher et al 2012 , 2013 ). Likewise, psyllids of the Western haplotype were identified across a large geographical range from California and New Mexico up to Washington, Oregon, and Idaho ( Swisher et al 2012 , 2013 ). To date, the Northwestern haplotype has only been identified in the Northwestern states of Washington, Oregon, and Idaho ( Swisher et al 2012 , 2013 ; data not shown).…”
mentioning
confidence: 99%
See 1 more Smart Citation